Non-invasive measurement of oil-water two-phase flow in vertical pipe using ultrasonic Doppler sensor and gamma ray densitometer - Abbagoni, Baba Musa; Yeung, Hoi; Lao, Liyun (Elsevier, 2021)
Oil–water two-phase flow experiments were conducted in a vertical pipe to study the liquid–liquid flow measurement using a non-invasive ultrasound Doppler flow sensor and a gamma-ray densitometer. Tap water and a dyed mineral oil are used as test the fluids. A novel Doppler effect strategy is used to estimate the mixture flow velocity in a vertical pipe based on flow velocity measured by the ultrasound sensor and the shear flow velocity profile model. Drift-flux flow model was used in conjunction phase fractions to predict the superficial velocities of oil and water. The results indicate that the proposed method estimated oil-continuous flow and water-continuous flow have average relative errors of 5.2% and 4.5%; and superficial phase flow velocities of oil and of water have average relative errors of 4.5% and 5.9% respectively. These results demonstrate the potential for using ultrasonic Doppler sensor combined with gamma densitometer for oil–water measurement.
Keywords: Liquid-liquid flow; Drift-flux model; Velocity profile; Water fraction; phase superficial velocity